(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
ABSTRACT This experience report aims to report how the inclusion of themes such as diversity and inclusion occurred in multidisciplinary activities during Operation Alto Vale, held in March 2016 in the municipality of Rio do Sul - SC, as well as the positive impacts generated for extension workers, students and public-school teachers.